Transportation carbon dioxide emission offsets by public urban trees: A case study in Bolzano, Italy (2015)
Increased carbon dioxide (CO2) emissions in urban areas due to rapid population growth and consequent increased energy use and vehicular traffic is a worldwide problem contributing to an altered global climate. Studies from North America and Asia have reported that urban trees can be used to mitigate these emissions. However, little is known about the role of European urban streetscapes in mitigating similar emissions from the transportation sector. Therefore, the aim of this study was to develop a method to calculate carbon dioxide storage and sequestration at the streetscapes level using field data, an existing tree inventory and available region-specific allometric equations. Results were compared to annual vehicular CO2 emissions from a city in the Italian Alps to determine the CO2 offset potential of urban streetscapes. We found that the trees in Bolzano's streetscapes through sequestration annually offset 0.08% of the amount of CO2 emitted by the transportation sector. Results, applications, and a potential indicator are discussed and compared against other studies. Findings from this study can be used as indicators and to better understand the potential role of urban streetscapes in reducing urban atmospheric CO2 emissions.